The tropical tortoise chelonoidis denticulata (Testudines: Testudinidae) from the late pleistocene of Argentina and its paleoclimatological implications - Manzano, Adriana Silvina (2009)
A new specimen that is represented by an almost complete and perfectly preserved plastron is described herein from the Late Pleistocene of Entre Rios Province, Argentina. The specimen represents the first fossil of the large-sized tortoise Chelonoidis denticulata and a range extension of at least 800 kilometers further south of its extant distribution. We determine the species, among others, based on large size, anteriorly projecting gulars, lack of any significant mid-body constriction, and especially the presence of a small inguinal scute. Together with various mammalian finds from the same locality, the new find allow the paleobiogeographic and paleoenvironmental inference that Entre Ríos Province was characterized by a subtropical temperate to warm and humid climate during the last interglacial period.